Correlations between mercury concentration, and stable isotope ratios of carbon and nitrogen of amino acids in scalp hair from whale meat eaters and heavy fish eaters. (28th March 2017) - Endo, Tetsuya; Ogasawara, Hideki; Hayasaka, Moriaki; Hotta, Yohei; Kimura, Osamu; Petzke, Klaus J.
Abstract : Rationale: As mercury (Hg) accumulation in marine animals generally increases with increased trophic level (δ 15 N values) through the food web, predators accumulate higher levels of Hg. The main source of human Hg intake is the consumption of fish and other marine animals, and Hg concentration in scalp hair is the preferred marker for evaluating consumption of marine animals. Difference in δ 15 N values between trophic and source amino acids of human consumers could enable us to estimate the trophic level of the consumer without knowing the bulk δ 15 N value of their prey. Methods: We measured the δ 15 N values of 15 amino acids in scalp hair from heavy fish eaters and whale meat eaters using isotope ratio monitoring gas chromatography/mass spectrometry (irm‐GC/MS), and investigated the correlations between Hg concentrations in the hair and the δ 15 N values of the individual constituent amino acids. Results: The δ 15 N values for all trophic amino acids (Ala, Val, Leu, Ile, Pro, Asx and Glx) increased with increases in Hg concentration ( p  < 0.01), with the highest correlation being with Glx (R 2  = 0.725). In contrast, the δ 15 N value for Thr decreased with increases in Hg concentration (R 2  = 0.663, p  < 0.01). The difference in δ 15 N values between Glx and Thr was positively correlated with Hg concentration, showing the highest correlation coefficient (R 2  = 0.773, p  < 0.01) among the various combinations for amino acids. Conclusions: The difference in δ 15 N values between Glx and Thr appears to be the best proxy for the estimation of Hg concentration in scalp hair. Copyright © 2017 John Wiley & Sons, Ltd.